2002
DOI: 10.1007/s00059-002-2340-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Heart Rate Variability in the Early Diagnosis of Diabetic Autonomic Neuropathy in Children

Abstract: HRV analysis can detect early subclinical alterations of the autonomic nervous system in asymptomatic patients with IDDM, which seem to consist mainly in a parasympathetic impairment. Autonomic dysfunction is associated both with the duration and an inadequate metabolic control of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
3
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 24 publications
6
62
3
2
Order By: Relevance
“…Our young subjects with short duration of diabetes did not display any clinical evidence of autonomic neuropathy or other complications. Conversely, other studies have reported that abnormal autonomic function at this age [33,34,35,36,37] is largely related to hyperglycaemia and elevated HbA 1 c. However, our data strongly indicate that spontaneous hypoglycaemia rather than hyperglycaemia is the more important determinant of prolonged QTc at night in type 1 diabetic children and adolescents. We have recently demonstrated similar changes during hypoglycaemia in adults [38].…”
Section: Discussioncontrasting
confidence: 78%
“…Our young subjects with short duration of diabetes did not display any clinical evidence of autonomic neuropathy or other complications. Conversely, other studies have reported that abnormal autonomic function at this age [33,34,35,36,37] is largely related to hyperglycaemia and elevated HbA 1 c. However, our data strongly indicate that spontaneous hypoglycaemia rather than hyperglycaemia is the more important determinant of prolonged QTc at night in type 1 diabetic children and adolescents. We have recently demonstrated similar changes during hypoglycaemia in adults [38].…”
Section: Discussioncontrasting
confidence: 78%
“…Subsequently, a fast Fourier transformation was applied. The spectral components of total power (TP), very low frequency (VLF, 0.003-0.04 Hz), low frequency (LF, 0.04-0.15 Hz) and high frequency (HF, 0.15-0.40 Hz) in normalized units (LF nu and HF nu, respectively) and in milliseconds squared were used [8][9][10][11][12][13]. We used the LF to HF ratio (LF/ /HF) as an index of cardiac sympathovagal balance.…”
Section: Heart Rate Analysismentioning
confidence: 99%
“…Neither the age of the patient nor the type of diabetes is a limiting factor. 3,[73][74][75] The connection between autonomic neuropathy and the duration of diabetes is still unclear. 2 In spite of the PERSPECTIVES Key: HRV = heart rate variability; ACE = angiotensin-converting enzyme frequently progressive course of the disease, symptoms and clinical signs of autonomic dysfunction in many type 1 and type 2 diabetics may be stable over some years.…”
Section: Cadn Progressionmentioning
confidence: 99%